Prevention of epithelial to mesenchymal transition in colorectal carcinoma by regulation of the E-cadherin-β-catenin-vinculin axis. (28th June 2019) - Pal, Ipsita; Rajesh, Y.; Banik, Payel; Dey, Goutam; Dey, Kaushik Kumar; Bharti, Rashmi; Naskar, Deboki; Chakraborty, Sandipan; Ghosh, Sudip K.; Das, Swadesh K.; Emdad, Luni; Kundu, Subhas Chandra; et al.
Abstract: Epithelial to mesenchymal transition (EMT) is compulsory for metastatic dissemination and is stimulated by TGF-β. Although targeting EMT has significant therapeutic potential, very few pharmacological agents have been shown to exert anti-metastatic effects. BI-69A11, a competitive Akt inhibitor, displays anti-tumor activity toward melanoma and colon carcinoma. This study provides molecular and biochemical insights into the effects of BI-69A11 on EMT in colon carcinoma cells in vitro and in vivo . BI-69A11 inhibited metastasis-associated cellular migration, invasion and adhesion by inhibiting the Akt-β-catenin pathway. The underlying mechanism of BI-69A11-mediated inhibition of EMT included suppression of nuclear transport of β-catenin and diminished phosphorylation of β-catenin, which was accompanied by enhanced E-cadherin-β-catenin complex formation at the plasma membrane. Additionally, BI-69A11 caused increased accumulation of vinculin in the plasma membrane, which fortified focal adhesion junctions leading to inhibition of metastasis. BI-69A11 downregulated activation of the TGF-β-induced non-canonical Akt/NF-κB pathway and blocked TGF-β-induced enhanced expression of Snail causing restoration of E-cadherin. Overall, this study enhances our understanding of the molecular mechanism of BI-69A11-induced reversal of EMT in colorectal carcinoma cells in vitro, in vivo and in TGF-β-induced model systems. Highlights: EMT promotes cell invasion and cell migration that drives metastasis. BI-69A11 attenuates migration, invasion and suppresses EMT. BI-69A11 inhibits Akt-mediated transport of β-catenin. BI-69A11 downregulates activation of the TGF-β-induced non-canonical Akt/NF-κB pathway. This study reveals the molecular mechanism of BI-69A11-induced reversal of EMT in CRC.